((2+can3) (can (52-30can3))/2 -(2+can3) (can(26-15can3) 01/10/2021 Bởi Reese ((2+can3) (can (52-30can3))/2 -(2+can3) (can(26-15can3)
Giải thích các bước giải : \(\begin{array}{l} \frac{{(2 + \sqrt 3 )\sqrt {52 – 30\sqrt 3 } }}{2} – \left( {2 + \sqrt 3 } \right)\sqrt {26 – 15\sqrt 3 } \\ = \frac{{2 + \sqrt 3 }}{2}.\sqrt {52 – 30\sqrt 3 } – \frac{{2 + \sqrt 3 }}{{\sqrt 2 }}.\sqrt {52 – 30\sqrt 3 } \\ = \sqrt {52 – 30\sqrt 3 } \left( {\frac{{2 + \sqrt 3 }}{2} – \frac{{2\sqrt 2 + \sqrt 6 }}{2}} \right)\\ = \sqrt {52 – 30\sqrt 3 } .\frac{{2 – 2\sqrt 2 – \sqrt 6 + \sqrt 3 }}{2}\\ = \sqrt {25 – 2.15.\sqrt 3 + 27} .\,\frac{{2(1 – \sqrt 2 ) + \sqrt 3 (1 – \sqrt 2 )}}{2}\\ = \sqrt {25 – 2\sqrt {25} \sqrt {27} + 27} \,\,.\,\,\frac{{(2 + \sqrt 3 )(1 – \sqrt 2 )}}{2}\\ = \sqrt {{{\left( {5 – 3\sqrt 3 } \right)}^2}} \,\,.\,\,\frac{{(2 + \sqrt 3 )(1 – \sqrt 2 )}}{2} = \frac{{\left( {5 – 3\sqrt 3 } \right)\left( {2 + \sqrt 3 } \right)\left( {1 – \sqrt 2 } \right)}}{2} \end{array}\) Bình luận
Giải thích các bước giải :
\(\begin{array}{l}
\frac{{(2 + \sqrt 3 )\sqrt {52 – 30\sqrt 3 } }}{2} – \left( {2 + \sqrt 3 } \right)\sqrt {26 – 15\sqrt 3 } \\
= \frac{{2 + \sqrt 3 }}{2}.\sqrt {52 – 30\sqrt 3 } – \frac{{2 + \sqrt 3 }}{{\sqrt 2 }}.\sqrt {52 – 30\sqrt 3 } \\
= \sqrt {52 – 30\sqrt 3 } \left( {\frac{{2 + \sqrt 3 }}{2} – \frac{{2\sqrt 2 + \sqrt 6 }}{2}} \right)\\
= \sqrt {52 – 30\sqrt 3 } .\frac{{2 – 2\sqrt 2 – \sqrt 6 + \sqrt 3 }}{2}\\
= \sqrt {25 – 2.15.\sqrt 3 + 27} .\,\frac{{2(1 – \sqrt 2 ) + \sqrt 3 (1 – \sqrt 2 )}}{2}\\
= \sqrt {25 – 2\sqrt {25} \sqrt {27} + 27} \,\,.\,\,\frac{{(2 + \sqrt 3 )(1 – \sqrt 2 )}}{2}\\
= \sqrt {{{\left( {5 – 3\sqrt 3 } \right)}^2}} \,\,.\,\,\frac{{(2 + \sqrt 3 )(1 – \sqrt 2 )}}{2} = \frac{{\left( {5 – 3\sqrt 3 } \right)\left( {2 + \sqrt 3 } \right)\left( {1 – \sqrt 2 } \right)}}{2}
\end{array}\)